No significant difference between Australian heat wave impacts of Modoki and eastern Pacific El Niño. Issue 10 (29th May 2017) - Loughran, Tammas F.; Perkins‐Kirkpatrick, Sarah E.; Alexander, Lisa V.; Pitman, Andrew J.
Abstract: The influence of two El Niño types on the frequency of summer heat wave days in Australia is investigated using both observations and an atmospheric climate model. The two basic spatial variants of El Niño are the traditional warming in the eastern equatorial Pacific (EP) and the Modoki variant that has its largest warming in the central equatorial Pacific. While impacts of Modoki El Niño on Australian precipitation can be quite distinct from EP El Niño, the impact on heat waves is still unknown. Using a set of ensemble simulations, we compare the influence of Modoki and EP sea surface temperature forcing on Australian heat waves. We find that there is minimal difference between the impact of Modoki and EP El Niños on heat waves over Australia, which implies that future studies on heat wave variability need not differentiate the two. Plain Language Summary: The warm sea surface current in the Pacific called El Niño can affect the climate across the entire planet. El Niño can have its highest temperatures in either the eastern Pacific or the central Pacific. Using computer simulations, we test whether these different types of El Niño can differently affect how often heat waves occur in Australia during summer. We find that there is very little difference between the two types. This means that the results on other studies of the effect of El Niño on heat waves may be reliable despite differences in the ability to accurately simulate both El Niño types. Key Points: In observations, Modoki El Niños appear to have very weak impacts on heat waves in Australia compared to eastern Pacific El Niños A large sample of climate model ensembles indicate that there is no difference in heat wave impacts between the El Niño types By bootstrapping the ensemble members, we find the observed difference from traditional El Niño is likely due to sampling error